Transcriptional Modulator Ifrd1 Regulates Osteoclast Differentiation through Enhancing the NF-κB/NFATc1 Pathway - Iezaki, Takashi; Fukasawa, Kazuya; Park, Gyujin; Horie, Tetsuhiro; Kanayama, Takashi; Ozaki, Kakeru; Onishi, Yuki; Takahata, Yoshifumi; Nakamura, Yukari; Takarada, Takeshi; Yoneda, Yukio; Nakamura, Takashi; et al. (Molecular and cellular biology, 2016)
Bone homeostasis is maintained by the synergistic actions of bone-resorbing osteoclasts and bone-forming osteoblasts. Here, we show that the transcriptional coactivator/repressor interferon-related developmental regulator 1 (Ifrd1) is expressed in osteoclast lineages and represents a component of the machinery that regulates bone homeostasis. Ifrd1 expression was transcriptionally regulated in preosteoclasts by receptor activator of nuclear factor κB (NF-κB) ligand (RANKL) through activator protein 1. Global deletion of murine Ifrd1 increased bone formation and decreased bone resorption, leading to a higher bone mass. Deletion of Ifrd1 in osteoclast precursors prevented RANKL-induced bone loss, although no bone loss was observed under normal physiological conditions. RANKL-dependent osteoclastogenesis was impaired in vitro in Ifrd1-deleted bone marrow macrophages (BMMs). Ifrd1 deficiency increased the acetylation of p65 at residues K122 and K123 via the inhibition of histone deacetylase-dependent deacetylation in BMMs. This repressed the NF-κB-dependent transcription of nuclear factor of activated T cells, cytoplasmic 1 (NFATc1), an essential regulator of osteoclastogenesis. These findings suggest that an Ifrd1/NF-κB/NFATc1 axis plays a pivotal role in bone remodeling in vivo and represents a therapeutic target for bone diseases.